Evaluasi Pola Pengasuhan Sistem Daring Taruna Politeknik Penerbangan Makassar - Idyaningsih, Nining (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
In this online care system, it is necessary to prepare an infrastructure in the form of a network and application platform. The part that will determine effectiveness in distance care. The objectives of this research are (a) Knowing the patterns of care for the online system at the Makassar Poltekbang (b) Knowing the caregivers in dealing with the online system of parenting (c) Knowing how much influence cellphones have on the interest in learning of Makassar Aviation Polytechnic (d) Knowing how much influence handphone for cadets’ discipline while in the dormitory. The method of collecting data is through interviews in the form of direct questions and answers to informants, representatives of caregivers and cadets, and with observations which are then continued with data analysis so that the data will be more focused on pre-determined problems. The technique used in analyzing for this research is descriptive qualitative.